Coronavirus disease 2019 with spontaneous pneumothorax, pneumomediastinum and subcutaneous emphysema, Franc (2020)
To our knowledge, Complications such as pneumomediastinum and/or pneumothorax during the course of COVID-19 remain rare and their mechanism is poorly described. We present a case of COVID-19 pneumonia associated with spontaneous pneumothorax, pneumomediastinum and subcutaneous emphysema in an immunocompetent patient with no past history of smoking or chronic obstructive pulmonary disease (COPD). The only risk factor of this patient was prolonged cough. We hypothesize the mechanism underlying the pneumomediastinum is the aggressive disease pathophysiology in COVID-19 with an incresead risk of alveolar damage.